Obesity Increases and Physical Activity Decreases Lower Urinary Tract Symptom Risk in Older Men: The Osteoporotic Fractures in Men Study - Parsons, J. Kellogg (2011)
BACKGROUND: Two potential targets for preventing chronic lower urinary tract symptoms (LUTS) in older men are obesity and physical activity. OBJECTIVE: To examine associations of adiposity and physical activity with incident LUTS in community-dwelling older men. DESIGN, SETTING, AND PARTICIPANTS: The Osteoporotic Fractures in Men Study (MrOS) is a prospective cohort of men ≥65 yr of age. MrOS participants without LUTS and a history of LUTS treatment at baseline were included in this analysis. MEASUREMENTS: Adiposity was measured with body mass index (BMI), physical activity with the Physical Activity Scale for the Elderly (PASE) and self-report of daily walking, and LUTS with the American Urological Association Symptom Index. RESULTS AND LIMITATIONS: The mean age (standard deviation [SD]) of the 1695 participants was 72 (5) yr at baseline. At a mean (SD) follow-up of 4.6 (0.5) yr, 524 (31%) of men reported incident LUTS. In multivariate analyses, compared with men of normal weight at baseline (BMI <25 kg/m(2)), overweight (BMI: 25.0–29.9 kg/m(2)) and obese (≥30 kg/m(2)) men were 29% (adjusted odds ratio [OR(adj)]: 1.29; 95% confidence interval [CI], 1.00–1.68) and 41% (OR(adj): 1.41; 95% CI, 1.03–1.93) more likely to develop LUTS, respectively. Men in the highest quartile of physical activity were 29% (OR(adj): 0.71; 95% CI, 0.53–0.97) and those who walked daily 20% (OR(adj): 0.80; 95% CI, 0.65–0.98) less likely than their sedentary peers to develop LUTS, adjusting for BMI. The homogeneous composition of MrOS potentially diminishes the external validity of these results. CONCLUSIONS: In older men, obesity and higher physical activity are associated with increased and decreased risks of incident LUTS, respectively. Prevention of chronic urinary symptoms represents another potential health benefit of exercise in elderly men.